Analyze the Financial Fund Management in the Financial Management of Public Institutions - Wang, Wenfan (Journal of Theory and Practice of Social Science, 2023)
Financial fund management in the financial management of institutions is the basis and premise to complete various activities, only the effective management of financial funds, in order to ensure the long-term development of institutions, especially in recent years the reform of institutions in-depth, facing the financial management of institutions in the financial management of institutions, the management of institutions must strengthen the control of funds, so as to mention High utilization rate of funds. Based on this, this paper describes the connotation of financial funds management in the financial management of institutions and the role of financial funds management in the financial management of institutions. The main problems and strategies of financial funds management in the financial management of institutions are discussed and analyzed in order to improve the efficiency of the use of financial funds in institutions.